2016
DOI: 10.1128/jcm.01580-16
|View full text |Cite
|
Sign up to set email alerts
|

New Panfungal Real-Time PCR Assay for Diagnosis of Invasive Fungal Infections

Abstract: The diagnosis of invasive fungal infections (IFIs) is usually based on the isolation of the fungus in culture and histopathological techniques. However, these methods have many limitations often delaying the definitive diagnosis. In recent years, molecular diagnostics methods have emerged as a suitable alternative for IFI diagnosis. When there is not a clear suspicion of the fungus involved in the IFI, panfungal real-time PCR assays have been used, allowing amplification of any fungal DNA. However, this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 30 publications
(28 reference statements)
0
40
0
Order By: Relevance
“…The preferred target(s) are one or more regions of the rRNA gene cluster -the internal transcribed spacers 1 and 2 (ITS1 and ITS2) and the D1/D2 regions of the 28S rRNA gene (Figure 1; White et al, 1990). Amplification is most often followed by DNA sequencing but high-resolution melt curve analysis in real-time PCR assays is increasingly used (Bezdicek et al, 2016;Valero et al, 2016). Together, these assays have successfully detected and identified fungi from diverse specimen types including fresh tissue, formalin fixed paraffin embedded (FFPE) tissue, cerebrospinal fluid (CSF), vitreous fluid, blood, and bronchoalveolar lavage fluid (BALF) (Lau et al, 2007;Landlinger et al, 2010;Bezdicek et al, 2016;Rahn et al, 2016;Rickerts, 2016;Valero et al, 2016;Gomez et al, 2017;Zeller et al, 2017;Sabino et al, 2019) with good accuracy and specificity though with varying sensitivity between specimen types.…”
Section: Panfungal Pcr Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferred target(s) are one or more regions of the rRNA gene cluster -the internal transcribed spacers 1 and 2 (ITS1 and ITS2) and the D1/D2 regions of the 28S rRNA gene (Figure 1; White et al, 1990). Amplification is most often followed by DNA sequencing but high-resolution melt curve analysis in real-time PCR assays is increasingly used (Bezdicek et al, 2016;Valero et al, 2016). Together, these assays have successfully detected and identified fungi from diverse specimen types including fresh tissue, formalin fixed paraffin embedded (FFPE) tissue, cerebrospinal fluid (CSF), vitreous fluid, blood, and bronchoalveolar lavage fluid (BALF) (Lau et al, 2007;Landlinger et al, 2010;Bezdicek et al, 2016;Rahn et al, 2016;Rickerts, 2016;Valero et al, 2016;Gomez et al, 2017;Zeller et al, 2017;Sabino et al, 2019) with good accuracy and specificity though with varying sensitivity between specimen types.…”
Section: Panfungal Pcr Assaysmentioning
confidence: 99%
“…Amplification is most often followed by DNA sequencing but high-resolution melt curve analysis in real-time PCR assays is increasingly used (Bezdicek et al, 2016;Valero et al, 2016). Together, these assays have successfully detected and identified fungi from diverse specimen types including fresh tissue, formalin fixed paraffin embedded (FFPE) tissue, cerebrospinal fluid (CSF), vitreous fluid, blood, and bronchoalveolar lavage fluid (BALF) (Lau et al, 2007;Landlinger et al, 2010;Bezdicek et al, 2016;Rahn et al, 2016;Rickerts, 2016;Valero et al, 2016;Gomez et al, 2017;Zeller et al, 2017;Sabino et al, 2019) with good accuracy and specificity though with varying sensitivity between specimen types. One study reported the best results when performed on sterile fluid specimens (including blood, CSF, and aspirates) with a sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) of 100, 96, 100, and 86%, respectively, but these values decreased to 90, 75, 86, and 82% from BALF (Zeller et al, 2017).…”
Section: Panfungal Pcr Assaysmentioning
confidence: 99%
“…Furthermore we did not want to withhold the two cases with positive blood cultures (for either C. albicans or C. parapsilosis) but negative PCR, as they show the limits of our assay's sensitivity, which is in line with the parameters reported for other in-house panfungal assays. These tests show sensitivities ranging from 69 to 96% [21,23,[26][27][28]30], and consist of up to seven individual multiplex PCRs [28]. The sensitivity of a panfungal PCR assay generally is lower than that of an assay targeting specific pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The SepsiTest™ is marketed by Molzym (Molzym Molecular Diagnostic, Bremen, Germany), and targets the 16S rRNA gene for bacteria, and the 18S rRNA gene for fungi. In addition to this assay, few research use only (RUO) tests like the Fungiplex Universal RUO PCR kit (Bruker Daltonik, Bremen, Germany) are commercially available, and a number of in-house panfungal assays have been described [21,[23][24][25][26][27][28][29][30]. We recently published a new panfungal HybProbe real-time PCR assay using the Light-Cycler instrument (Roche), which targets the complete fungal ITS2 region [31].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this, pan-fungal PCR assays have been developed, and while they have been shown to be more sensitive than culture to identify the infecting species, they are not fully sensitive for dematiaceous fungi. 29 One must be careful when interpreting positive PCR in the setting of negative culture and microscopy as they may represent contaminants that are not clinically relevant. 30 Using PCR to amplify the D1/D2 domains of 28S rDNA has also been shown to be useful in identifying dematiaceous fungi.…”
Section: Diagnosismentioning
confidence: 99%